Increasing Customer Loyalty Through Digital Marketing, Corporate Image, Mobile Banking Service Quality and Shariah Compliance - Romadhoni, Buyung; Amin, Asbi; Rahmawati, Sitti (International Journal of Scientific Research and Management (IJSRM), 2025)
The purpose of this research is to provide a deeper understanding of the factors that shape customer loyalty in Islamic banking, including Digital Marketing, Corporate Image, Quality of mobile banking services and Shariah Compliance. The type of research used in this study is a type of associative explanatory research, which aims to find out the relationship between two or more variables. The population that will be taken in this study is all customers who transact with PT Bank Syariah. The population in this study uses an infinite population, where the infinite population in this study is taken from the customer of PT Bank Syariah Indonesia KCP Makassar Panakukang. Because the exact number of the population is unknown, the sampling technique used is accidental sampling, where 100 respondents are selected based on chance encounters with researchers, according to Rao Purba's formula so that 100 samples are obtained. The results of this study show that Digital marketing, mobile service quality and Shariah compliance. However, the results of this study prove that corporate image does not have a significant influence on the loyalty of Islamic bank customers.